THE ROLE OF REPENTANCE OF CONVICTS IN THE PROCESS OF THEIR CORRECTION AND RESOCIALIZATION - Klishevich, Nataliia; Sulitskyi, Vadym (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
At present, the humanization of the State Penitentiary Service of Ukraine is carried out through the development and implementation of milder measures of punishment, reduction of sentences for certain crimes, the introduction of alternatives to imprisonment, such as probation. All this requires more serious and comprehensive socio-psychological research on the development and implementation of a wide range of pedagogical and socio-psychological methods of influencing the personality, group, team of convicts. Promising, in our opinion, is the psychological change in the personality of the convict by bringing him to sincere conscious repentance, reconciliation with the victim. This approach will help to correct the convict and positively influence his resocialization and create conditions for successful socialization. The purpose of our study was to determine the role and place of repentance in the process of serving a sentence by convicts and to identify the positive impact of repentance on correction and resocialization, reducing the risk of repeated wrongful acts by persons serving sentences in penal institutions. To achieve this goal, we used the following methods: analysis of scientific literature, observation, questioning, psychodiagnostics testing, extended interviews. The study was conducted in the period from 2010 to 2016 in the correctional colonies of the Donetsk region. It was attended by 3,400 clients of correctional system and 280 employees of penitentiary institutions. In the course of our research, we discovered: at present, views on the concept of "repentance" can be divided into creative, religious, philosophical, socio-psychological, pedagogical, legal; the legal interpretation of the concept of "effective repentance" and its application in the practice of justice revealed a number of problems that require solution; repentance in the psychological and pedagogical sense can be viewed as: an integral part of moral self-improvement; the acquisition of a new spiritual, moral, psychological quality of the person; the life position of the individual in relation to the world, people, his own place in life; the formation of other positive, socially recognized values; an indicator of moral maturity, spiritual and mental health.In this article we offer our own view on the role and place of repentance in the process of correction and resocialization of clients of correctional system. Scientific research of this problem is very important in a methodological sense not only for the penitentiary service, including the work of psychologists in penitentiary institutions, but also for social educators and social workers. It will contribute to the solution of general and special issues of the psychological and pedagogical process of the execution of sentences by employees of penitentiary institutions and the social and psychological process of serving sentences by convicts, will help create reliable conditions for the protection of human rights, civil liberties, including people who are serving sentences.